Association between PXR polymorphisms and cancer risk: a systematic review and meta-analysis. Issue 3 (12th June 2018) - Wen, Jing; Lv, Zhi; Ding, Hanxi; Fang, Xinxin; Sun, Mingjun
Abstract : Current studies have explored the correlation between the single nucleotide polymorphisms (SNPs) of pregnane X receptor ( PXR ) and cancer risk. However, the findings were conflicting. Hence, we performed a comprehensive review and meta-analysis for these researches to determine the effect of PXR polymorphisms on the risk of cancer. Eligible publications were collected based on a series of rigorous inclusion and exclusion criteria. In consequence, a total of eight case–control studies (from seven citations) covering 11143 cases and 12170 controls were involved in a meta-analysis of ten prevalent PXR SNPs (rs10504191 G/A, rs3814058 C/T, rs6785049 A/G, rs1464603 A/G, rs1523127 A/C, rs2276706 G/A, rs2276707 C/T, rs3732360 C/T, rs3814055 C/T, rs3814057 A/C). The correlations between PXR SNPs and cancer risk were estimated by odds ratios (ORs) with their 95% confidence intervals (95%CIs). The findings demonstrated that rs3814058 polymorphism (CT compared with CC: pooled OR = 1.280, P =6.36E-05; TT compared with CC: pooled OR = 1.663, P =2.40E-04; dominant model: pooled OR = 1.382, P =2.58E-08; recessive model: pooled OR = 1.422, P =0.002; T compared with C: pooled OR = 1.292, P =6.35E-05) and rs3814057 polymorphism (AC compared with AA: pooled OR = 1.170, P =0.036; dominant model: pooled OR = 1.162, P =0.037) were associated with the risk of overall cancer. In stratified analyses, rs3814058 polymorphism was revealed to increase the cancer risk in lung cancer subgroup. In summary, this meta-analysis indicates that the rs3814057 and rs3814058 polymorphisms of PXR gene play crucial roles in the pathogenesis of cancer and may be novel biomarkers for cancer-forewarning in overall population or in some particular subgroups.